Homophily, Echo chamber, Affective polarization and radicalization against the migration: Case study #Openarms on Twitter - Castillo-de-Mesa, Joaquín; Méndez-Domínguez, Paula (My University, 2020)
The Mediterranean sea is one of the deadliest migration routes in the world and has once again become a political enclave with the Spanish humanitarian ship called “Open Arms”. This ship was institutionally blocked during a nineteen days cruise, and involved in diplomatic disputes in the divisions in the EU. Media echoed this humanitarian crisis and reopened the debate of migration and asylum policies, especially through Twitter. This social network was used by European politicians to defend and detect their political position and ideas. In reaction to the event and the political positions, citizenship was expressed massively. Various social actors and the NGO OpenArms itself also made use of this social network to request a safe landing, urgent evacuations, manifest and show through multimedia content the situation they were in. The online reaction of the public opinion to this “refugee crisis” has been observed through the netnography and social networks analysis, identifying leaderships. It has been detected communities and social distance through certain algorithms. The results show ideologically similar online communities that leads to affective polarization. The social-emotional online interaction drives to the emergence of collective emotional states, which ends up affecting online behaviors that are shown in conducts in the offline field.
Keywords: Información - Manipulación; Migraciones - Mediterráneo; Crisis migratoria; Redes sociales online; Twitter; Homofilia; Desinformación; Polarización afectiva